SOLUTION: If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the second equation. 3x + y +

Algebra ->  Algebra  -> Coordinate Systems and Linear Equations -> SOLUTION: If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the second equation. 3x + y +      Log On

 Ad: You enter your algebra equation or inequality - Algebrator solves it step-by-step while providing clear explanations. Free on-line demo . Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Linear Solvers Practice Answers archive Word Problems Lessons In depth

 Question 633345: If you were to use the substitution method to solve the following system, choose the new system of equations that would result if x was isolated in the second equation. 3x + y + 2z = 1 x + 2y – z = –8 3x – y – 3z = 18Answer by Maths68(1474)   (Show Source): You can put this solution on YOUR website!3x + y + 2z = 1...............(1) x + 2y – z = –8...............(2) 3x – y – 3z = 18..............(3) Take (2) x + 2y – z = –8 x=z-2y-8......................(4) Substitute the value of x in (1) 3x + y + 2z = 1...............(1) 3(z-2y-8) + y + 2z = 1 3z-6y-24+y+2z=1 -5y+5z-24=1 -5y+5z=1+24 -5y+5z=25 5(-y+z)=25 5(-y+z)/5=25/5 -y+z=5........................(5) Substitute the value of x in (3) 3x – y – 3z = 18..............(3) 3(z-2y-8)-y-3z=18 3z-6y-24-y-3z=18 3z-3z-6y-y=18+24 -7y=42 -7y/-7=42/-7 y=-6 Put the value of y in (5) -y+z=5........................(5) -(-6)+z=5 6+z=5 z=5-6 z=-1 Put the value of y and z in (4) x=z-2y-8......................(4) x=-1-2(-6)-8 x=-1+12-8 x=12-9 x=3 x,y,z=3,-6,-1 Check ===== Put the value of x,y,z in (1) 3x + y + 2z = 1...............(1) 3(3)+(-6)+2(-1)=1 9-6-2=1 9-8=1 1=1 Put the value of x,y,z in (2) x + 2y – z = –8...............(2) 3+2(-6)-(-1)=-8 3-12+1=-8 4-12=-8 -8=-8 Put the value of x,y,z in (3) 3x – y – 3z = 18..............(3) 3(3)-(-6)-3(-1)=18 9+6+3=18 18=18